The New Intergovernmentalism and the Euro Crisis: A Painful Case? - Dermot Hodson (London School of Economics and Political Science (LSE), European Institute, 2019)
The new intergovernmentalism seeks to understand the changing dynamics of contemporary European integration. It emphasises, inter alia, member states' preference for deliberative modes of decision-making and their reluctance to delegate new powers to traditional supranational institutions. The euro crisis is sometimes seen as a difficult case for the new intergovernmentalism because of the perceived importance of hard bargaining over crisis measures during this episode and the new roles entrusted to the European Commission and the European Central Bank under crisis reforms. Such criticisms, this paper argues, overlook: the importance of high-level consensus-seeking and deliberation in saving the single currency; the disparate forms of delegation deployed to preserve member state influence over Economic and Monetary Union; and the extent to which the euro crisis has amplified the European Union's political disequilibrium. Far from running counter to the new intergovernmentalism, it concludes, the euro crisis exemplifies the turbulent dynamics of the post-Maastricht period.
Keywords: 330; European integration; euro crisis; integration theory; new intergovernmentalism